New Human Follitropin Preparations: How Glycan Structural Differences May Affect Biochemical and Biological Function and Clinical Effect - Dias, James A.; Ulloa-Aguirre, Alfredo (Frontiers in Endocrinology, 2021)
It is well accepted that pituitary follitropin is secreted into the circulation as a mixture of variants, which do not differ in primary structure but rather at the level of glycosylation. These glycosidic forms vary in the number of glycosylation sites filled, complexity of glycosidic chains, and sialylation and sulfation. It is generally agreed that high sialylation, 2,3 sialic acid capping terminal N-acetyl galactosamine or galactose leads to longer circulating half-life, by virtue of blocking binding by Ashwell’s lectin (in the liver). Seemingly in contrast, 2,6 sialic acid found in humans does not prevent recognition of galactose and N-acetyl galactosamine by the asialoglycoprotein receptor (ASGR, Ashwell’s lectin). Few studies on clinical outcomes comparing differences in sialylation of commercially available preparations, are available. Recently absence of FSH glycosylation which occurs naturally and varies as women age, and primarily on the β- subunit, has emerged as a key modifier of follitropin action, with profound biological effects in vivo in animal models. Limited examination of this characteristic in commercially available follitropin recombinant hormone preparations is available. Thus, most of the observations that have been well characterized biochemically have been tested in vitro, with engineered non gonadal host cells bearing recombinant receptors or in animal models. Since limited studies in human granulosa cells are available, a question is whether structural differences in commercially available follitropin affects biological function and clinical effect in humans. The presence of fucose for example has not been studied greatly though in the case of antibody therapy it has a large effect on targeting. This review from the biochemical/structural point of view reflects on this question and is assessed in the context of available published data. If clinical differences are to be expected or not, the readers will have a better understanding of the evidence and limitations of such expectations. All these observations beg the question whether in practice, structural differences pale in comparison to the “art” of controlled ovarian hyperstimulation, the genetic context of the patient and reliance of steroid production as the main real time biomarker.